ASSESSMENT OF TOTAL INTRAVENOUS ANESTHESIA BY PROPOFOL AND INHALATIONAL ANESTHESIA WITH ISOFLURANE FOR CONTROLLED HYPOTENSION IN FUNCTIONAL ENDOSCOPIC SINUS SURGERY - LAVANYA, POOSARLA VENKATA SURYA; GANESH, MYLAPURAM VENKATA; LAVANYA, KAKI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study’s key objective is to compare the propofol-based total intravenous anesthesia (TIVA) with isoflurane-based inhalational anesthesia for controlled hypotension during functional endoscopic sinus surgery (FESS). Methods: This study was a prospective randomized and controlled single-blinded clinical study. The study involved 40 patients posted for elective FESS surgery, selected randomly from the ENT department. Anesthesia was induced with Inj. Midazolam 2 mg, Inj. Fentanyl 2 μg/kg, Inj. Propofol 2 mg/kg, Inj. Vecuronium 0.1 mg/kg was ventilated using oxygen, air, and Isoflurane (FiO2 of 0.5) in patients with isofurane. Injections of 2 mg of midazolam, 2 μg/kg of fentanyl,2 mg/kg propofol, and 0.1 mg/kg vecuronium, as well as oxygen and air for ventilation, were used to induce anesthesia (FIO2 of 0.5) in TIVA group patients. Fromme boezaart scale was used as an evaluation scale for surgical site bleeding. Results: The average blood loss in the isoflurane group was 134.25±4.65 ml and in the propofol group was 66.95±4.28 ml. The quality of the surgical field in the propofol group is (3.13±0.9), and in the isoflurane group is (3.13±0.8). The results are significant. Conclusion: Total intravenous anesthesia using propofol provides notable advantages over the traditionally used inhalational anesthetic technique using isoflurane in surgical field conditions and intraoperative blood loss.